2023
DOI: 10.3389/fimmu.2023.1200201
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomes in the development of the immune microenvironment in hepatocellular carcinoma

Abstract: Despite numerous improved treatment methods used in recent years, hepatocellular carcinoma (HCC) is still a disease with a high mortality rate. Many recent studies have shown that immunotherapy has great potential for cancer treatment. Exosomes play a significant role in negatively regulating the immune system in HCC. Understanding how these exosomes play a role in innate and adaptive immunity in HCC can significantly improve the immunotherapeutic effects on HCC. Further, engineered exosomes can deliver differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 240 publications
0
3
0
Order By: Relevance
“…They play a crucial role in the physiological processes of cellular formation, growth, differentiation, and aging in human cells, particularly in relation to the development, metastasis, and progression of cancer [ 20 ]. Numerous studies have substantiated the exact regulation of exosome synthesis, secretion, transport, uptake, and release through unique signaling pathways, which in turn exert an influence on the growth and immunosuppression of HCC [ 21 ]. In this section, we explore the mechanisms by which HCC cells generate and release exosomes to facilitate intercellular communication and modulate microenvironmental conditions, as well as the composition and functions of these extracellular vesicles ( Figure 1 ).…”
Section: Exosomes and Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…They play a crucial role in the physiological processes of cellular formation, growth, differentiation, and aging in human cells, particularly in relation to the development, metastasis, and progression of cancer [ 20 ]. Numerous studies have substantiated the exact regulation of exosome synthesis, secretion, transport, uptake, and release through unique signaling pathways, which in turn exert an influence on the growth and immunosuppression of HCC [ 21 ]. In this section, we explore the mechanisms by which HCC cells generate and release exosomes to facilitate intercellular communication and modulate microenvironmental conditions, as well as the composition and functions of these extracellular vesicles ( Figure 1 ).…”
Section: Exosomes and Hccmentioning
confidence: 99%
“…However, in cancer tissue, tumor cells possess the ability to deceive immune cells and escape immune surveillance, resulting in immunosuppression and cancer development [ 49 ]. The effects of exosomes on HCC encompass decreasing immune cell activity, facilitating the apoptosis of CD8+ T lymphocytes, eliciting the activation of regulatory T cells (Tregs), and leading to Th17/Treg imbalance [ 1 , 12 , 21 , 24 ]. Several studies found that the highly abundant exosomal 14-3-3 ζ protein can inhibit the activation, proliferation, and differentiation of T cells, inducing their transformation into Tregs, which causes protumor immune response [ 50 ].…”
Section: Exosomes and Hccmentioning
confidence: 99%
“…Within the context of HCC, EVs have emerged as key players in the intricate network of intercellular communication within the tumor microenvironment [15,145,146]. These vesicles carry a cargo of bioactive molecules with the capacity to profoundly influence various aspects of HCC progression [109], encompassing tumor growth [147], immune evasion mechanisms [148,149], and resistance to therapeutic interventions. The distinctive composition of EV cargo, enriched with HCC-specific biomolecules, offers an attractive avenue for targeted therapeutic strategies [11].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal circRNAs have been reported to reshape the tumor microenvironment by prompting hypoxic stress response, stimulating angiogenesis ( 36 ), contributing to metabolic reprogramming ( 37 , 38 ), facilitating inflammatory changes in the HCC cells ( 39 ) and inducing tumor immunosuppression. The exosomes secreted by HCC cells carry circRNA into immune cells, which intervene in the activation of immune cells and promote the overexpression of immune checkpoints to regulate immune response, leading tumor cells to acquire immunosuppressive properties ( 40 ). Furthermore, immunosuppression is the final result of a combination of TME-related factors, including hypoxia, angiogenesis, metabolic reprogramming, and inflammation changes.…”
Section: Hcc-derived Exosomal Circrnas Remodel the Tmementioning
confidence: 99%